Implementation of Inhabitant Housing Rehabilitation Program in Improving Community Welfare - Daraba, Dahyar; Arimbi, Sita; Dione, Frans; Niswaty, Risma (PINISI Discretion Review, 2018)
The house is one of the basic human needs The purpose of this study was to determine the implementation of development in the rehabilitation program for uninhabitable housing in Pangkalpinang City. Researchers use this type of qualitative research with a descriptive-inductive approach to reveal facts and events in the field. Data collection techniques used observation, documentation and interviews. The results of this study indicate that the implementation of the rehabilitation program for uninhabitable housing construction in the City of Pangkalpinang has been pursued optimally. But in reality the implementation of the program still has some obstacles so that the achievement of the program does not go according to plan. This is due to the lack of participation from the community with program involvement, there are still many people who have not met the criteria as potential recipients of assistance due to lack of administration and limited facilities.